ANALYSIS OF ENERGY-EFFICIENT TECHNOLOGIES OF PRODUCTION OF MEDICINAL PRODUCTS - ТАРАСЕНКО, Г. В.; ЗМІЄВСЬКА, І. С.; САЛІЙ, О. О.; ПОПОВА, М. Е. (Technologies and Engineering, 2024)
Purpose. Conducting an analysis of modern pharmaceutical production technologies and substantiating practical measures regarding the use of energy-efficient technologies in order to optimize and minimize energy consumption while preserving and guaranteeing the quality of finished products. Methodology. Analytical review of scientific, scientific-practical and statistical-analytical literature for the purpose of systematization and optimization of data that can be used for energy saving at enterprises of the pharmaceutical industry. Findings. The structure of energy consumption of the pharmaceutical industry was studied and ways of optimizing the energy efficiency of drug production were analyzed, which can be implemented both at the levels of individual stages, operations, processes, systems, and for the enterprise as a whole. A systematic analysis of production technologies and technological processes was carried out, ways of their optimization were proposed to minimize energy consumption and increase energy efficiency while maintaining the quality of finished products and increasing their competitiveness on the market. Originality. The theoretical aspects of energy-saving measures of pharmaceutical production are substantiated, ways of optimization and improvement of their energy efficiency, intensification of production processes, optimization of design and control of production processes and technological systems to achieve the cumulative effect of saving energy resources are proposed. Practical value. Determining measures to increase the energy efficiency of pharmaceutical production will allow to reduce energy consumption during production, to introduce measures for constant monitoring and control of consumed energy in order to ensure uninterrupted production processes and avoid reduction in the volume of production of medicines due to interruptions in energy supply.